2011
DOI: 10.17221/72/2010-pps
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storage on redgram (Cajanus cajan /L./ Millsp) and greengram (Vigna radiata /L./ Wilczek) with particular reference to lipid composition

Abstract: Gopinath M.R., Sambiah K., Niranjana S.R. (2011) The effects of storage on the lipid composition of three redgram (TTB-7, BRG-1, and ICP-8863) and three greengram (PUSA BISAKI, KDM-1, and CHINA MOONG) varieties were studied. Environment variables such as temperature and relative humidity were recorded during storage period. Moisture content was found to increase along with the percent incidence of storage insects. The incidence of storage moulds and insects was recorded in all the samples; results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…The maximum increase of free fatty acid was recorded in aluminium box and minimum increase was observed in cotton bag. The results are in line with the finding of Gopinath et al (2011) [7] , reported that free fatty acid content increased during storage in red gram and green gram. Increases free fatty acid contents were observed during the storage with infestation of other legumes such as cowpea (Ojimelukwe et al, 1999) [21] .…”
Section: Resultssupporting
confidence: 92%
“…The maximum increase of free fatty acid was recorded in aluminium box and minimum increase was observed in cotton bag. The results are in line with the finding of Gopinath et al (2011) [7] , reported that free fatty acid content increased during storage in red gram and green gram. Increases free fatty acid contents were observed during the storage with infestation of other legumes such as cowpea (Ojimelukwe et al, 1999) [21] .…”
Section: Resultssupporting
confidence: 92%
“…Gopinath et.al. 16 found that storage fungi depleted total fat (1.94-1.75g), triglycerides (1.46-1.07g), where as phospholipids (0.06-0.21g), free fatty acids (0.002-0.01 g) and peroxide values increased. The fatty acid content of palmitic, steric, linoleic acid decreased, but oleic acid content increased in Red Gram and Black gram during storage periods.…”
Section: Resultsmentioning
confidence: 97%
“…All countries must heed the warnings of the 'union of concerned scientists' to protect the earth for future generations. [14][15][16][17][18][19][20][21][22]…”
Section: Resultsmentioning
confidence: 99%